L'effet des additifs sur le comportement mécanique d'un matériau composite (Polyester insaturé renforcé par les fibres Alfa) - MOUSSAOUI, Imane. DERRADJ, Nour El houda (UNIVERSITE MOHAMED BOUDIAF - M’SILA, 2021)
The compound was prepared using Alfa fibers a s a reinforcement of the unsaturated polyester matrix and pouder of marble as an additive, the aim of this study is to improve the mechanical behavior of this compound. Plant fibers are characterized by high physical and chemical properties that are abundant in nature light weight biodegradability and low cost these properties made vegetable fibers competitive with synthetic fibers in the preparation of compounds, to improve the surface of the Alfa fibers we treated them with benzoyl at a concentration 9%, permanganate 0.2%, soda at a concentration of 9% for 24 h, and soda at a concentration of 9% and put it in the microwave for 10 min. The results obtained from the tests carried out on the composite and the fibers showed that the treatment with sodium hydroxide at a concentration of 9% for a period of 24 h had the effect of Improving the mechanical properties of the composite and the fibers by compared to untreated fibers and other treatments, and it also proved that the added pouder of marble had a prominent effect in improving the mechanical behavior. Diagnostic tests used in this study: tensile test, infrared spectrum.
Keywords: unsaturated polyester, composite materials، Stipa Tenacissima, Tensile strength.